The role of women in sustaining the cultural identity of Mah Meri / Nur Ruzanna Harun - Harun, Nur Ruzanna (2015)
Women playa fundamental role in the development of civilization. They do not only playa major role in the formation of the next generations, but also contribute to the development and survival of civilization. Their rights are protected and guaranteed by the national law without discriminations either as a majority or minority group.However, their role is not only important as a mother and a wife to help the husbands but also important in the family institution and the community. This group is seen as a major party in protecting and maintaining their cultural identity. The objective of this study was to identify the role of women and to analyze their contributions to the culture and economy of the the Mah Meri tribe in detail. This study utilized a qualitative research approach using an ethnographic research design to explore the role of women in the Mah Meri tribe. The findings of this study found that the Mah Meri women did not only playa role as a wife and mother but also playa role in increasing economic resources and maintain the culture of the Mah Meri tribe. This group started to venture into entrepreneurship by marketing handicrafts made of woven. Therefore,for subsequent studies, the proposed approach was suitable for upgrading their handicrafts and raise awareness among the Mah Meri youths community to protect and preserve the cultural heritage from being lost in the midst of development and modernization.